Women's Perspective on Using Tinder: A User Study of Gender Dynamics in a Mobile Device Application - VOGEL, CARL (New York: ACM, 2017)
Mobile applications expand possibilities for interaction and extend the boundaries of communication. Regarding online dating, Tinder is one of those applications that make it easier to connect people, and it brings out a new concept of relationship in which emotional bonds are established in a virtual space. However, it is relevant to investigate whether Tinder enables women’s empowerment and how the user-mobile device interaction and the graphical user interface bear upon gender dynamics. Forty women were interviewed and the findings show that Tinder is not meeting women’s expectations, rather it is stimulating the objectification of women. Considering that online dating is a growing trend and that it can be a revolutionary tool to connect people, we analysed the interface and pointed out some issues that should be considered to enhance women’s experience.
SIGDOC '17 Proceedings of the 35th ACM International Conference on the Design of Communication
PUBLISHED
Halifax, Nova Scotia, Canada
Keywords: Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS; Creative Technologies; Digital Humanities; Intelligent Content & Communications; Computational linguistics